Tall enough? : an illustrator’s visual inquiry into the production and consumption of isiXhosa picture books in South Africa - Morris, Hannah (Stellenbosch : University of Stellenbosch, 2008)
Thesis (Mphil (Visual Arts. Illustration))--University of Stellenbosch, 2007.